PEMANFAATAN MIDDLEWARE ROBOT OPERATING SYSTEM (ROS) DALAM MENJAWAB TANTANGAN REVOLUSI INDUSTRI 4.0 - Jalil, Abdul (ILKOM Jurnal Ilmiah, 2019)
The industrial revolution 4.0 is the development of industrial based on the internet, control, robotics, and networking. This study describes the usage of a Robot Operating System (ROS) middleware to answer the challenges of the industrial revolution 4.0 for control the industrial electronic devices and household electronic equipment using Raspberry Pi. ROS has nodes, topics and messages that can be used to manage the Raspberry Pi GPIO pins to be active high (1) or active low (0). The result of this study is the system be able to control the on and off electronic devices through the GPIO pins of Raspberry Pi and relay module based on message commands from the ROS node. The electronic devices had controlled in this study are a fan, light, air conditioner, and room heater that have 110/220 AC voltage.